2020
DOI: 10.1021/acs.jpcc.0c05728
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Growth Mechanism of Self-Assembled Nanowires on Pt-Deposited Ge(001) via Scanning Tunneling Microscopy and Density Functional Theory Calculations

Abstract: Shrinking the size of electronic components has been highly desirable in the semiconductor industry in recent years, and the next breakthrough in reducing the size of electronic devices may be via the bottom-up approach. Previous research showed that the deposition of metal atoms onto semiconductor surfaces could result in the self-assembly of atomically thin nanowires (NWs) extending for hundreds of nanometers. However, current understanding of the self-assembly mechanism of the NWs on semiconductor surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Early studies revealed that the deposition of Pt or Au atoms on pristine Ge(001) substrates could trigger the self-assembly of well-ordered nanowires (NWs) extending for hundreds of nanometers. Substantial efforts have been devoted to investigate the NWs on Pt-modified Ge(001). Their atomic structures and growth mechanism had been established. However, the atomic configurations of NWs on the Au-modified Ge(001) surfaces remain elusive, and their electronic behaviors have long been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies revealed that the deposition of Pt or Au atoms on pristine Ge(001) substrates could trigger the self-assembly of well-ordered nanowires (NWs) extending for hundreds of nanometers. Substantial efforts have been devoted to investigate the NWs on Pt-modified Ge(001). Their atomic structures and growth mechanism had been established. However, the atomic configurations of NWs on the Au-modified Ge(001) surfaces remain elusive, and their electronic behaviors have long been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported the self-assembly of atomic NWs on semiconductor surfaces after annealing at an elevated temperature. , Among those nanostructures on Si or Ge platforms, Au-NWs on Ge(001) surfaces have attracted significant attention due to their elusive atomic configurations and ambiguous electronic behaviors. Much effort has been devoted to deciphering their atomic configurations, and many structural models were then proposed. , Previously, we reported different types of NWs on Au/Ge(001) surfaces based on scanning tunneling microscopy (STM) observations and identified two structural models, i.e., Au-NWs-in-trenches (ANT) and Au–Ge-modified-dimer-row (AGMDR), with the DFT calculation evaluation …”
mentioning
confidence: 99%